Clinical Outcomes of Remission Induction Therapy for Severe Antineutrophil Cytoplasmic Antibody–Associated Vasculitis. Issue 9 (26th August 2013) - Miloslavsky, E. M.; Specks, U.; Merkel, P. A.; Seo, P.; Spiera, R.; Langford, C. A.; Hoffman, G. S.; Kallenberg, C. G. M.; St.Clair, E. W.; Tchao, N. K.; Viviano, L.; Ding, L.; et al.
Abstract : Objective: To evaluate the reasons that complete remission is not achieved or maintained with original treatment in some patients with antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis (AAV) treated with rituximab (RTX) or with cyclophosphamide/azathioprine (CYC/AZA). Methods: The Rituximab in AAV trial was a randomized, double‐blind, placebo‐controlled trial comparing the rate of remission induction among patients treated with RTX (n = 99) and patients treated with CYC followed by AZA (n = 98). Glucocorticoids were tapered over a period of 5 months. The primary outcome measure was lack of disease activity without glucocorticoid treatment at 6 months. To determine the most important reason for failure to achieve the primary outcome, 7 hierarchical categories of reasons were defined retrospectively (uncontrolled disease, adverse event leading to therapy discontinuation, severe flare, limited flare, Birmingham Vasculitis Activity Score for Wegener's Granulomatosis >0, prednisone treatment at any dosage, and other). Results: Although remission (lack of disease activity) was achieved in 170 of the 197 patients (86%) in the first 6 months, the primary outcome measure was not achieved in 42%. There were 3 deaths. Twenty‐four percent of the patients failed to achieve the primary end point due to active disease: 10 (5%) experienced uncontrolled disease in the first month and 37 (19%) experienced flares after initial improvement. In the majority of such patients, treatment with blinded crossover or according to best medical judgment led to disease control. Ninety‐one percent of patients who had uncontrolled disease or experienced a severe flare had proteinase 3 (PR3)–ANCA. When patients with uncontrolled disease were excluded from analysis, those who were PR3‐ANCA positive were found to experience fewer flares when treated with RTX compared to CYC/AZA (8 of 59 [14%] versus 20 of 62 [32%]; P = 0.02). Neither ANCA titers nor B cell counts predicted disease flare. Conclusion: Current treatment regimens are largely successful in controlling AAV, but in approximately one‐fourth of patients, active disease persists or recurs in the first 6 months despite treatment. PR3‐ANCA positivity is a risk factor for recurrence or persistence of severe disease. ANCA titers and B cell detectability are poor predictors of both disease relapse and disease quiescence in the first 6 months.